Proceedings of the 7th Workshop on Cognitive Modeling And Computational Linguistics (CMCL 2017) 2017
DOI: 10.18653/v1/w17-0701
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Reduction correlates with temporal lobe activity

Abstract: Using the Entropy Reduction incremental complexity metric, we relate high gamma power signals from the brains of epileptic patients to incremental stages of syntactic analysis in English and French. We find that signals recorded intracranially from the anterior Inferior Temporal Sulcus (aITS) and the posterior Inferior Temporal Gyrus (pITG) correlate with wordby-word Entropy Reduction values derived from phrase structure grammars for those languages. In the anterior region, this correlation persists even in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In a recent ECoG study, Nelson, Karoui, et al (2017) showed that bigram word entropy during sentence reading is negatively related with fluctuations in the high gamma (70-150 Hz) power on electrodes overlying left 60 posterior temporal regions. In a separate analysis of the same dataset, entropy reduction (changes in word-by-word syntactic uncertainty) was found to have a positive linear relationship with high gamma power in the left anterior and posterior inferior temporal electrode sites (Nelson, Dehaene, Pallier, & Hale, 2017). 65 Although fMRI work provided insights into spatial fingerprints of probabilistic computations and work in electrophysiology showed their temporal and high-frequency neural characteristics during sentence reading, it is as of yet unclear whether these statistical quantities are also reflected in ongoing electrophysiological activity during natural language listening.…”
mentioning
confidence: 86%
“…In a recent ECoG study, Nelson, Karoui, et al (2017) showed that bigram word entropy during sentence reading is negatively related with fluctuations in the high gamma (70-150 Hz) power on electrodes overlying left 60 posterior temporal regions. In a separate analysis of the same dataset, entropy reduction (changes in word-by-word syntactic uncertainty) was found to have a positive linear relationship with high gamma power in the left anterior and posterior inferior temporal electrode sites (Nelson, Dehaene, Pallier, & Hale, 2017). 65 Although fMRI work provided insights into spatial fingerprints of probabilistic computations and work in electrophysiology showed their temporal and high-frequency neural characteristics during sentence reading, it is as of yet unclear whether these statistical quantities are also reflected in ongoing electrophysiological activity during natural language listening.…”
mentioning
confidence: 86%
“…The entropy reduction hypothesis has been applied to both naturalistic text stimuli (Frank, 2013; Wu, Bachrach, Cardenas, & Schuler, 2010) and controlled experimental materials (Linzen & Jaeger, 2015). A number of studies have also shown that it correlates with measured reading times and neural signals related to sentence‐medial ambiguities, including those observed in processing RCs (Chen, Jäger, & Hale, 2012; Frank, 2013; Lowder, Choi, Ferreira, & Henderson, 2018; Nelson, Dehaene, Pallier, & Hale, 2017; Yun, Chen, Hunter, Whitman, & Hale, 2015). In the next section, we review some of the most crucial experimental findings in RC processing and discuss in detail the predictions made by different processing principles.…”
Section: Principles Proposed To Account For Rc Processingmentioning
confidence: 97%
“…Complexity is non-linear and complex to define but is often computationally quantified with entropy measurements. Sample entropy, proposed by Richman and Moorman (Richman and Moorman, 2000 ), is a well-defined index of complexity and has been applied to brain activity (Yao et al, 2013 ; Wang et al, 2014 , 2017 ; Lebedev et al, 2016 ; Li et al, 2016 ; Zhou et al, 2016 ; Jia et al, 2017 ; Nelson et al, 2017 ; Chang et al, 2018 ; Song et al, 2018 ). It is noteworthy that multiscale entropy (MSE) analysis (Costa et al, 2002 , 2005 ; Yang and Tsai, 2013 ; Courtiol et al, 2016 ) calculates a series of sample entropy over multiple time scales, which captures the temporal complexity characteristcs of time-series neural signals from microscopic to macroscopic aspects.…”
Section: Introductionmentioning
confidence: 99%